OPTIMALISASI PENGAWASAN UNIT AMC TERHADAP KELAYAKAN GSE DI SISI UDARA BANDAR UDARA INTERNASIONAL HANG NADIM BATAM - Amrullah Fattah; Anton Budiarto; Laila Rochmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The problem of monitoring performance of AMC personnel on the airside of Hang Nadim International Airport, Batam still many GSE vehicles whose operating year exceeds the specified limits. In this case, the author uses a qualitative descriptive method with PM 91 of 2016 concerning the age limitation of ground support equipment on the air side as the theoretical basis in this study. The results of this study can be concluded that as a solution to the problems that researchers are experiencing is to improve the quality of AMC personnel by providing training and training to obtain a license or reactivate a member's license that is no longer active and for the operation of the garbarata it must be immediately given to a suitable third party to operate it.